Responses of aphid parasitoids to aphid sex pheromones: laboratory and field studies - Glinwood, Robert Thomas (1998)
The behavioural responses of aphid parasitoids (Hymenoptera: Braconidae: Aphidiinae) to aphid sex pheromones were investigated in the laboratory and field. In a wind tunnel bioassay, Aphidius eadyi, Aphidius rhopalosiphi, Diaeretiella rapae, Ephedrus plagiator, Praon myzophagum and Praon volucre responded to the aphid sex pheromone components nepetalactone and nepetalactol. P. myzophagum reared on two different host aphid species showed different responses to combinations of nepetalactone and nepetalactol in the wind tunnel, indicating that long term laboratory rearing may influence parasitoid responses to aphid sex pheromones. The ability of two aphid parasitoids to learn aphid sex pheromones through prior exposure in the presence of host aphids was investigated. The generalist E. plagiator showed evidence of associative learning, whereas the specialist Aphidius ervi did not. When A. ervi was exposed to the pheromone without contact with host aphids, the parasitoid response was reduced by habituation. Exposure to aphid sex pheromone during laboratory host attack trials had no effect on the host attack behaviour of A. ervi. In laboratory cage experiments, aphid sex pheromone lures increased the retention of A. rhopalosiphi, but not by Praon volucre, on aphid-infested plants. In a wind tunnel bioassay, aphid sex pheromone enhanced the attraction of A. ervi to a plant-host complex. In the field, aphid sex pheromone lures increased parasitisation rates by A. rhopalosiphi and P. volucre on aphid-infested potted plants. A series of potted plant experiments indicated that the pheromone may increase parasitisation of aphids by A. rhopalosiphi, but not P. volucre, at a distance of 1m away from the lure. The effect of baiting plots of winter wheat with aphid sex pheromone was investigated in two field experiments. In 1996, the number of parasitoid mummies was higher in baited plots than in unbaited plots, and the synchrony between aphid and parasitoid populations was closer in baited plots. In 1997, aphid sex pheromone had no effect on parasitisation levels. The results are discussed in the context of developing a novel aphid control strategy based on the use of aphid sex pheromones to manipulate parasitoid populations.